Phytochemical and Pharmacognosy study of Cassia tora (Chakramarda) Medicinal plant of Leguminosae family (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The present study investigates the phytochemical and pharmacognostic characteristics of Cassia tora L. (Chakramarda), a medicinal plant widely distributed across Rajasthan, India. Taxonomically classified under the Fabaceae family, Cassia tora is commonly found as a weed during the rainy season. The plant exhibits distinct morphological features including an erect, foetid herbaceous structure with yellow flowers and falcate pods. Detailed macro- and microscopic analyses of the root and stem reveal characteristic features such as lignified vascular tissues, presence of calcium oxalate crystals, and various types of parenchyma, xylem, and phloem tissues. Powder microscopy of the whole plant demonstrates diagnostic elements like scalariform and spiral xylem vessels, starch grains, septate fibers, trichomes, and stone cells. Additionally, chromatographic analysis using winCATS software showed consistent results across three tracks, each dominated by a primary peak (~87–90% area), indicating the presence of a major phytoconstituent, with several minor peaks suggesting additional components yet to be identified. These findings support the pharmacognostic authentication and chemical profiling of Cassia tora, and further studies involving reference standards or mass spectrometry are necessary for comprehensive compound identification.